Linking business strategies with upgrading pathways in global value chains: Insights from the Kenyan solar market. (17th November 2022) - Hansen, Ulrich Elmer; Bhamidipati, Padmasai Lakshmi; Pedersen, Mathilde Brix; Nygaard, Ivan; Njoroge, Hope Nyambura
Summary: Motivation: Research on global value chains (GVCs) has tended to overlook the agency of the local firm when it comes to processes of upgrading. Purpose: We attend to this knowledge gap by exploring the relationship between the business strategies and upgrading pathways of 14 firms operating in the value chain for solar systems in Kenya. Methods and approach: The article draws on in‐depth fieldwork carried out in Kenya, which included 30 semi‐structured interviews with firm representatives and industry informants. Findings: We find that local firms pursue different upgrading pathways in order to be competitive and we show the underlying business strategies whereby firms pursue different upgrading pathways. Policy implications: The article contributes to overcoming the prevailing black‐boxing in the GVC literature on local firms undergoing processes of upgrading.